Direction Wedding Photography In Creating Visual Aesthetic Creations - Adie Alfariz N; Nuruzzaman nuruzzaman; Aghnia Dian Lestari (International Journal Labs, 2024)
This research examines the crucial role of Direction Wedding Photography in Creating Visual Aesthetic Creations that meet contemporary expectations and trends in the wedding photography industry. The aim of this research is to analyze the key factors that influence the success of wedding photography, identify innovative techniques used by professional photographers, and understand the role of social media and digital platforms in shaping client preferences and expectations. Through a qualitative approach with descriptive analysis, this research explores the perspectives of professional photographers and clients to understand the complex dynamics in producing aesthetic and meaningful wedding photography work. The research results reveal that success in wedding photography depends on the integration of several key factors: technical expertise, artistic sensibility, effective communication and adaptability to contemporary trends. Photographers are required to master innovative techniques such as strobist lighting systems and optical manipulation using prism rod glass, which allows them to produce visual images that are not only documentary but also artistic. The analysis shows that visual aesthetics in wedding photography is a subjective concept, involving the photographer's personal interpretation and the client's individual preferences. Furthermore, this research reveals the significant impact of social media and digital platforms in shaping client preferences and expectations. So Direction Wedding Photography in the contemporary era is a complex synthesis of technical expertise, artistic creativity, emotional intelligence, and a deep understanding of socio-technological dynamics.